Math, asked by arbaazhussain0611, 8 months ago

(sec- A-1)² - (tanA - sinA)² = (1-cosA)²​

Answers

Answered by Ves1857
1

Refer attachment for your answer...

Attachments:
Answered by Ataraxia
10

To Prove :-

\sf (secA-1)^2-(tanA-sinA)^2 = (1-cosA)^2

Solution :-

\sf L.H.S = (secA-1)^2- (tanA-sinA)^2= ( 1-cosA)^2

        = \sf sec^2A+1-2secA -(tan^2A+sin^2A-2tanAsinA ) \\\\= sec^2A+1-2secA-tan^2A-sin^2A+2tanAsinA \\\\= (sec^2A-tan^2A)+(1-sin^2A)-2secA+2tanAsinA

\bullet \bf \ sec^2-tan^2A= 1 \\\\\bullet \ 1-sin^2A = cos^2A

        = \sf 1+cos^2A-2secA+2tanAsinA \\\\= 1+cos^2A -2(secA+tanAsinA)

\bullet \bf \ secA= \dfrac{1}{cosA} \\\\\bullet \ tanA = \dfrac{sinA}{cosA}

      = \sf 1+cos^2A -2 \left( \dfrac{1}{cosA} +\dfrac{sinA}{cosA} \times sinA \right) \\\\= 1+cos^2A- 2 \left( \dfrac{1-sin^2A}{cosA} \right)  \\\\= 1+cos^2A -2 \times \dfrac{cos^2A}{cosA} \\\\= 1+cos^2A - 2cosA \\\\= (1-cosA)^2\\\\= R.H.S

Hence proved.

Similar questions